+0

# simplify

0
105
1

simplify

(3x2+9x-1)+(-5x2+6x-10)

A. 8𝑥2 − 3𝑥 + 9

B. −2𝑥2 − 3𝑥 + 9

C. 8𝑥2 + 15𝑥 − 11

D. −2𝑥2 + 15𝑥 − 11

Guest Aug 29, 2017

#1
+5227
+3

(3x2 + 9x - 1) + (-5x2 + 6x - 10)

We can get rid of the parenthesees since there is only addition between them.

=  3x2 + 9x - 1 + -5x2 + 6x - 10

Now we can rearrange the terms so like terms are together.

=  3x2 - 5x2 + 9x + 6x - 1 - 10

Combine like terms. Just like  3 apples - 5 apples = -2 apples ....so does  3x2 - 5x2 = -2x2

=      -2x2     +  15x        - 11

hectictar  Aug 29, 2017
Sort:

#1
+5227
+3

(3x2 + 9x - 1) + (-5x2 + 6x - 10)

We can get rid of the parenthesees since there is only addition between them.

=  3x2 + 9x - 1 + -5x2 + 6x - 10

Now we can rearrange the terms so like terms are together.

=  3x2 - 5x2 + 9x + 6x - 1 - 10

Combine like terms. Just like  3 apples - 5 apples = -2 apples ....so does  3x2 - 5x2 = -2x2

=      -2x2     +  15x        - 11

hectictar  Aug 29, 2017

### 2 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details